Evolution of Technology-Enhanced Alternative Preparation for Special Education Teachers. (September 2019) - Hager, Karen D.; Fiechtl, Barbara J.
In this article, we describe the evolution of a statewide alternative teacher preparation program for teachers of students with disabilities and explain current processes to revise and expand the program to increase accessibility to teacher candidates in rural schools. We will identify important features of the program including (a) significant collaboration with Local Education Agencies, (b) the combination of synchronous and asynchronous course delivery to increase accessibility, and (c) embedded supports for alternative preparation teacher candidates completing a distance learning program, as well as describe the process and collaboration involved in revising the program to increase accessibility and efficiency, while retaining quality. Ongoing challenges to delivering effective alternative preparation programs that are accessible to individuals in rural schools and potential solutions to these challenges are provided.